2011
DOI: 10.1007/s11270-011-0924-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vertical-Flow Constructed Wetlands for Swine Wastewater Treatment

Abstract: In this study, the role of Cyperus sp. was evaluated for removal of pollutants from swine wastewater. Vertical-flow pilot scale constructed wetlands (CWs) operating with a hydraulic retention time (HRT) of 72 h were monitored in a greenhouse, located in Viçosa, Brazil. Significant differences were observed for the following parameters: Kjeldahl nitrogen, total phosphorus, alkalinity and electric conductivity, with averages removals of 37.5 and 28.5%, 55.9 and 44.4%, 30.2 and 25.6 and 26.1% and 22.9% (for plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
3
9
1
1
Order By: Relevance
“…A correlation coefficient r of 0.97 was observed between the CoD removal percentages and the abundances of aerobic bacteria in the three-step series CRi system, indicating that the correlation was very obvious. This also indicated that microbes were playing a key role in the removal of organic matter, which was in agreement with some previous studies [10][11][12][13][14][15].…”
Section: Distribution Of Aerobic Ammonifying Bacteriasupporting
confidence: 93%
“…A correlation coefficient r of 0.97 was observed between the CoD removal percentages and the abundances of aerobic bacteria in the three-step series CRi system, indicating that the correlation was very obvious. This also indicated that microbes were playing a key role in the removal of organic matter, which was in agreement with some previous studies [10][11][12][13][14][15].…”
Section: Distribution Of Aerobic Ammonifying Bacteriasupporting
confidence: 93%
“…Nevertheless, the average TKN removal did not change significantly (p>0.05) ( Table 3). A satisfactory efficiency of TKN removal was obtained for all systems in the three operation phases, with values higher than those observed by Sarmento et al (2012) when treating swine wastewater in VFCWs (28 to 37%) and a removal of 17%observed by Vymazal & Kröpfelová (2011) in the initial two months of VFCW monitoring in the domestic sewage treatment.…”
Section: Resultsmentioning
confidence: 78%
“…Based on the analyses results, the nutrients/Na accumulation by Tifton 85 bermudagrass was calculated using Eq 1 [ 19 ]. where, A TN, K, TP or Na —nutrient or Na accumulation (g), CNutri—content of nutrients or Na in dry matter of the aerial part of Tifton 85 bermudagrass (g g -1 ); DMY—dry matter of the aerial part of Tifton 85 bermudagrass.…”
Section: Methodsmentioning
confidence: 99%